From Mexico to South Carolina: a study of undocumented women (De México a Carolina del Sur: una investigación de mujeres indocumentadas) - Sellers Campbell, Wendy
Undocumented women are part of a new and growing population in the southeastern United States. This study looks at the question around the process that undocumented women take in their journey to South Carolina through looking at their lives in Mexico, the journey to the United States, the quality of present lives, and the hopes for the future. Data was collected in South Carolina through interviews with 20 undocumented women from Mexico using a grounded theory approach. Interviews were conducted in Spanish, audio-recorded, and transcribed. The results show that the journey to the United States is a four-phase process including the migration northward, arrival in South Carolina, working and living in the Southeast, and a possible return to Mexico. Throughout the process, the women have demonstrated strength and resiliency in overcoming barriers and building a new life for themselves and their families in South Carolina, but the importance of transnationalism is apparent as the women continue to maintain strong connections with sending communities in Mexico. The findings suggest that more research is necessary regarding resiliency and longitudinal processes of migration in the southeastern United States. Results contribute to the literature on Latinos in South Carolina and in the southeastern United States.